The Role of Lactate Metabolism in Tumorsa a Minireview (London Journal of Engineering Research, 2023)
As an important product of glycolysis, lactate plays a crucial role in mitochondrial oxidative metabolism and gluconeogenesis. Lactate not only provides energy as a substrate to support cell growth and development but also acts as an important signaling molecule to affect the biochemical functions of proteins in cells, thereby regulating the corresponding biological functions. An important feature of energy metabolism in tumor cells is known as the Warburg effect, which is characterized by a heavy reliance on glycolysis and the production of large amounts of lactate. Scientists have successively reported that lactic acid (lactate with extra protons) is associated with cancer growth and immune suppression. But a new study shows for the first time that lactic acid promotes anti-tumor immunity by increasing CD8+ T cells in multiple tumor models1. This interesting discovery has led to a whole new understanding of the role of lactate in tumors. In this review, we not only summarize the role of lactate in the pathophysiological process of tumors but also further discuss new therapeutic modalities.
Keywords: tumor; therapy; lactate; Warburg effect